2010
DOI: 10.1128/jvi.02675-09
|View full text |Cite
|
Sign up to set email alerts
|

β1Integrin Expression Increases Susceptibility of Memory B Cells to Epstein-Barr Virus Infection

Abstract: Epstein-Barr virus (EBV) uses nasal mucosa-associated lymphoid tissue (NALT) as a portal of entry toEpstein-Barr virus (EBV) is a ubiquitous human gammaherpesvirus that is transmitted via saliva and infects more than 90% of the world's population (21). Much of EBV's medical importance relates to its association with B-cell malignancies, including Burkitt's lymphoma, Hodgkin's lymphoma, and posttransplant lymphoproliferative disease (21). The oncogenic potential of EBV is clearly illustrated by its unique capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…More recently, Dorner et al also reported that naïve (CD27 − ) and total memory (CD27 + ) B cells from tonsils were equally infectable in short-term assays, although subsequently naïve cells grew slightly quicker and gave slightly better LCL yields from limiting dilution seedings [48]. While naïve (CD27 − ) cells from peripheral blood resembled their tonsillar counterparts, they were more infectable than peripheral blood memory (CD27 + ) preparations; this could not be explained at the level of receptor (CD21)/co-receptor (HLAII) expression but was ascribed to heterogeneity among circulating memory cells in expression of another putative co-receptor, α5β1 integrin [49]. Comparisons with the present work are difficult because Dorner et al employed an unusual recombinant EBV strain (lacking one of the latent proteins, LMP2A) whose low titre preparations necessitated the use of spinoculation to achieve measurable rates of infection.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Dorner et al also reported that naïve (CD27 − ) and total memory (CD27 + ) B cells from tonsils were equally infectable in short-term assays, although subsequently naïve cells grew slightly quicker and gave slightly better LCL yields from limiting dilution seedings [48]. While naïve (CD27 − ) cells from peripheral blood resembled their tonsillar counterparts, they were more infectable than peripheral blood memory (CD27 + ) preparations; this could not be explained at the level of receptor (CD21)/co-receptor (HLAII) expression but was ascribed to heterogeneity among circulating memory cells in expression of another putative co-receptor, α5β1 integrin [49]. Comparisons with the present work are difficult because Dorner et al employed an unusual recombinant EBV strain (lacking one of the latent proteins, LMP2A) whose low titre preparations necessitated the use of spinoculation to achieve measurable rates of infection.…”
Section: Discussionmentioning
confidence: 97%
“…Integrins are involved in the entry of many viruses (2,5,19,21,26,34,36,44,59,64) and bacteria (16,27,40). The pathogen-host interaction may promote the clustering of integrins and focal adhesion formation but subvert the downstream signaling network to modify membrane traffic and cytoskeletal dynamics to meet their own needs (1,17).…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of growth factor receptor activation, integrin engagement, and virus entry is beginning to emerge as a common theme in herpesvirus entry (89). Furthermore, integrins have also been shown to be important for the entry of memory B cells and epithelial cells (18,27). While it is the BMRF2 and gH/gL glycoproteins that have been implicated in the integrin interactions mediating these EBV entry events, it remains possible that the gB disintegrin-like domain may also play a role in coordinating integrin engagement, growth factor signaling, and virus entry.…”
Section: Discussionmentioning
confidence: 99%